A new model of knowledge and innovative capability development for small born–global bio–tech firms: evidence from the East Midlands, UK. (10th April 2015) - Simba, Amon
In the last two decades, the rapid transformation in information and communication technologies together with the adoption of more liberal structures governing trade as well as the modularisation of production and services has resulted in the proliferation of small born–global bio–tech firms. The firms have an international flair and they rapidly globalise their operations. Their strategic intent is to develop unique innovative capabilities through networking. In science–based industries such as the biotechnology sector the ability to innovate can only occur if a firm is able to both generate and integrate knowledge from inside and outside its boundaries. In that respect, this article employs a multi–case approach to construct a frame of reference for developing innovative capabilities that complement firm–based competences. The main focus is on small born–global bio–tech firms in the East Midlands region of the UK. The newly developed framework is invaluable to researchers, small born–global bio–tech and large bio–pharmaceutical firms. More so, it contributes to the concepts of dynamic capabilities and networking.